Community Knowledge in Waste Management at Lemahmekar and Plumbon, Indramayu Regency - Ira Puspita Windiari; Mutiara Salsabiela; Nurlaili Fauziah (IHSA Institute, 2022)
Garbage is the remains that have been taken as the main part or have undergone certain treatments. Some people view waste as material that is no longer used. From environmental management point of view, waste is an element/substance that can cause pollution to environmental sustainability. This study using questionnaire which given to 60 household. Respondents were determined using the Simple Random Sampling technique. The results of community knowledge in Lemahmekar and Plumbon showed different results. The level of community knowledge in Lemahmekar show the high category with a percentage of 63.33 %. Meanwhile, the level of community knowledge in Plumbon show low category with a percentage of 63.33 %. This means, people in Lemahmekar have better knowledge on waste management than the people in Plumbon. Based on the results of the Spearman's Correlation test, it shows that the level of education has an influence on knowledge of waste management with a value of +0.651 and +0.826, both of which indicate the level of correlation in a positive direction. This shows that the higher a person's education level, the better knowledge of waste management will be.